European Variscan orogenic evolution as an analogue of Tibetan‐Himalayan orogen: Insights from petrology and numerical modeling. Issue 7 (29th July 2016) - Maierová, P.; Schulmann, K.; Lexa, O.; Guillot, S.; Štípská, P.; Janoušek, V.; Čadek, O.
Abstract: The European Variscan orogeny can be compared to the Tibetan‐Himalayan system for three main reasons: (1) The Variscan belt originated through progressive amalgamation of Gondwanan blocks that were subsequently squeezed between the Laurussia and Gondwana continents. Similarly, the Tibetan‐Himalayan orogen results from amalgamated Gondwanan blocks squeezed between Asia and India. (2) The duration of the collisional period and the scale of the two orogens are comparable. (3) In both cases the collisional process resulted in formation of a thick crustal root and long lasting high‐pressure granulite facies metamorphism. Recent petrological data allow a more detailed comparison pointing to similarities also in the midcrustal re‐equilibration of the granulites and their association with specific (ultra)potassic magmatic rocks. In both orogens, the origin of the granulites was attributed to relamination and thermal maturation of lower crustal allochthon below upper plate crust. Subsequent evolution was explained by midcrustal flow eventually leading to extrusion of the high‐grade rocks. We propose that the lower and middle crustal processes in hot orogens are connected by gravity overturns. Such laterally forced gravity‐driven exchanges of material in the orogenic root were already documented in the Variscides, but the recent data from Tibet and Himalaya show that this process may have occurred also elsewhere. Using numerical models, we demonstrate that the exchange of the lower and middle crust can be efficient even for a minor density inversion and various characteristics of the crustal layers. The modeled pressure‐temperature paths are compatible with two‐stage metamorphism documented in Tibet and Himalaya. Key Points: P‐T and geochemical data from Tibet‐Himalaya and European Variscides show striking similarities Similarities are in (ultra)potassic magmatism and in two‐stage metamorphic evolution of lower crust Modeling shows that evolution of the lower crust can be explained by gravity‐driven exchanges